SeroprevalensiTrichinellosispadaBabi di Kota Kupang, Provinsi Nusa Tenggara Timur (SEROPREVALENCE OF TRICHINELLOSIS ON PIG AT KUPANG CITY, PROVINCE OF NUSA TENGGARA TIMUR) - Angi, Andrijanto Hauferson; Satrija, Fadjar; Lukman, Denny Widaya; Sudarwanto, Mirnawati; Sudarnika, Etih (Jurnal Veteriner, 2015)
Trichinellosisis is a zoonotic disease caused by infection of Trichinella spp. and is found world-wide.The seroprevalence of trichinellosis in pig population has never been reported in East Nusa TenggaraProvince particularly Kupang City. The aim of this study was to determine the seroprevalence oftrichinellosis in pig at Kupang City, East Nusa Tenggara. A cross-sectional study was conducted byexamining 376 blood samples of pigs collected from slaughterhouses in Oeba, Kupang using simplerandom sampling method. Blood samples were tested by indirect enzyme linked immunosorbent assay(ELISA) using Screen®Trichinella indirect multi-species ELISA kit. Test results showed that 3 (0.8%)serum samples were positive of trichinella antibody. In conclusion ,some pigs in the city of Kupang hasbeen infected by Trichinella sp. and could be a threat for human health.
Keywords: cross sectional study, indirect ELISA, seroprevalence, trichinellosis